Dietary lipid level and source affect metabolic responses in hybrid catfish (Pseudoplatystoma reticulatum × Leiarius marmoratus) - Paulino, Renan Rosa; Fortes-Silva, Rodrigo; Prieto-Guevara, Martha Janeth; Rodrigues, Edgar Junio Damasceno [UNESP]; Costa, Leandro Santos; Alves, Angélica Priscila do Carmo; Oliva Teles, Aires; Rosa, Priscila Vieira (Hindawi, 2020)
This study was undertaken to evaluate the effect of dietary lipid source [linseed oil (LO, rich in 18:3 n−3); corn oil (CO, rich in 18:2 n−6); olive oil (OO, rich in 18:1n−9); and fish oil (FO, rich in LC-PUFA)] and level (9% L and 18% L) on growth, body composition and selected plasma biochemistry parameters in hybrid catfish (Pseudoplatystoma reticulatum × Leiarius marmoratus) juveniles. Moreover, liver histology (lipids, glycogen, cell vacuolization) and key metabolic enzyme activities were also evaluated. After 8 weeks of feeding, there were no differences in growth performance and whole-body composition between groups. Plasma lipoprotein, muscle and liver composition, and G6PD and ME activity were affected by lipid level and source. No differences were observed between groups in hepatic ALT activity; however, AST activity was lower in fish fed the 9% L diets. Overall, liver and muscle fatty acid composition reflected that of diet FA composition, with increased n3/n6 ratio, high HUFA and low MUFA in fish fed FO compared with the VO diets. Higher liver glycogen content was observed in fish fed the 18% L than the 9% L diets, except for fish fed FO diet. Considering the experimental diets used, these results indicate that hybrid catfish can efficiently utilize VO supplementation as an energy source, without affecting growth performance and fillet composition.
Keywords: intermediary metabolism; lipid profile; lipoprotein; liver histology; triglycerides; vegetable oils